1985
DOI: 10.1029/ja090ia05p04099
|View full text |Cite
|
Sign up to set email alerts
|

A new source of suprathermal O+ ions near the dayside polar cap boundary

Abstract: A new dayside source of O+ ions for the polar magnetosphere is described, and a statistical survey presented of upward flows of O+ ions using 2 years of data from the retarding ion mass spectrometer (RIMS) experiment on board DE 1, at geocentric distances below 3 RE and invariant latitudes above 40°. The flows are classified according to their spin angle distributions. It is believed that the spacecraft potential near perigee is generally less than +2 V, in which case the entire O+ population at energies below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(113 citation statements)
references
References 50 publications
6
107
0
Order By: Relevance
“…Hultqvist, 1991) have demonstrated that the high-latitude terrestrial ionosphere is a significant hot plasma source for the magnetosphere. The two most important ionospheric outflow regions are the auroral region and the dayside cleft; statistical studies by Yau et al (1984) and Lockwood et al (1985) concluded that the auroral ionosphere is the major source of magnetospheric 0+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Hultqvist, 1991) have demonstrated that the high-latitude terrestrial ionosphere is a significant hot plasma source for the magnetosphere. The two most important ionospheric outflow regions are the auroral region and the dayside cleft; statistical studies by Yau et al (1984) and Lockwood et al (1985) concluded that the auroral ionosphere is the major source of magnetospheric 0+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…For an introduction and recent reviews, see Yau and André (1997); André and Yau (1997); Moore et al (1999). A particularly important source of upflowing ionospheric ions is the cleft ion fountain (Lockwood et al, 1985) associated with the ionospheric projection of the polar cusp/cleft. The exact relation between ionospheric upflow in the cusp as measured by incoherent scatter radar (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This possibly relates to polar rain, as described by Newell and Meng, though it is more likely polar wind created by upwelling ionospheric plasma (e.g. Lockwood et al, 1985). Figure 3c shows the distribution for average ion energies ranging from 2.10 to 4.85 keV.…”
Section: Dcr Average Ion Energy Occurrence Distributions and Comparismentioning
confidence: 99%
“…One such source of ionospheric plasma is the polar wind. In the region of the cusp, the cleft ion fountain also populates the magnetosphere with O + and H + ions, particularly during active times (Shelley, 1986;Lockwood et al, 1985;Hultqvist et al, 1988). Ionospheric outflow has been observed in the auroral regions in the form of ion beams and conics with energies of 0.1 to 10 keV (e.g.…”
Section: Data Processing and Presentationmentioning
confidence: 99%